Penerapan Sistem Informasi Akuntansi Pada Perusahaan Putra Jaya Kemasan - Rosita Nur Awaliyah; Dilla Salsabilla; Siti Nuraisyah; Afifah Nadiatul Muslihah; Oon Feriyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study evaluates the accounting system at a packaging printing service company, Putra Jaya Kemasan. Jaya Kemasan. The findings highlight some continuities and discrepancies between theory and practice in sales, purchasing, inventory, and payroll activities. practice in sales, purchasing, inventory, and payroll activities. It was found that although the company has had structured procedures, there are constraints such as less than optimal separation of functions, the use of semi-computerized accounting systems, and discrepancies in recording transactions. discrepancies in recording transactions. The research was conducted using qualitative methods through interviews, documentation, and observation at Putra Jaya Kemasan. Suggestions are given to improve the separation of functions, strengthen the authorization and recording system, and encourage the implementation of sound practices. implementation of sound practices. In conclusion, the company needs improvements in /implementation of accounting information systems to optimize operations and internal control.